1971
DOI: 10.1042/bj1240171
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic studies of flavoproteins and non-haem iron proteins of submitochondrial particles of Torulopsis utilis modified by iron- and sulphate-limited growth in continuous culture

Abstract: 1. A spectroscopic resolution has been made of the components contributing to the ;iron-flavoprotein' trough extending from 450 to 520nm in the reduced-minus-oxidized difference spectrum of submitochondrial particles of Torulopsis utilis. 2. Seven components were identified other than cytochrome b, ubiquinone and succinate dehydrogenase. On the basis of the effects of iron- and sulphate-limited growth of cells on their subsequently derived electron-transport particles, and also by consideration of analytical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Schuurmans Stekhoven (1 966) showed that yeast mitochondria can oxidize NADPH with respiratory control. Also submitochondrial particles can oxidize NADPH (Ragan & Garland, 1971 ;Djavadi et al, 1980). Direct oxidation of exogenous NADPH seems a general property of plant and fungal mitochondria (Palmer & Msller, 1982).…”
Section: P M B R U I N E N B E R G J P V a N D I J K E N A mentioning
confidence: 99%
“…Schuurmans Stekhoven (1 966) showed that yeast mitochondria can oxidize NADPH with respiratory control. Also submitochondrial particles can oxidize NADPH (Ragan & Garland, 1971 ;Djavadi et al, 1980). Direct oxidation of exogenous NADPH seems a general property of plant and fungal mitochondria (Palmer & Msller, 1982).…”
Section: P M B R U I N E N B E R G J P V a N D I J K E N A mentioning
confidence: 99%
“…4 According to the substrate screening performed by Kunz and Kunz,18 additions of glycerol-3-phosphate, proline and choline to rat liver mitochondria did not result in noticeable decrease in the°uorescence of non-NADlinked°avoproteins, which indicates that the°a-voenzymes glycerol-3-phosphate dehydrogenase (glycerol-3-phosphate:ubiquinone oxidoreductase), proline dehydrogenase and choline oxidase cannot be monitored by°uorescence. The experiments by Ragan and Garland 21 corroborate this by showing that, although the glycerol phosphate oxidase activity of submitochondrial particles from Torulopsis utilis is high, its substrate only causes a paradoxical°a vin°uorescence increase, although the concomitant absorbance decrease in the \°avin through" region denotes°avin reduction. A plausible explanation is that the°uorescence increase was due to a decrease in the internal¯lter e®ect at the°avin excitation band, revealing the°uorescence of other (oxidized)°avoproteins.…”
Section: Fluorescent Flavin Becomes a Compartment-speci¯c Mitochondrimentioning
confidence: 77%
“…A plausible explanation is that the°uorescence increase was due to a decrease in the internal¯lter e®ect at the°avin excitation band, revealing the°uorescence of other (oxidized)°avoproteins. 21 The rest of°avoproteins are reducible with dithionite only. [18][19][20][21] An additive contribution of FpL and ETF on°avin°uorescence is probably the cause of the extreme°avin°uo-rescence decrease (by taking the anoxia response as a reference) upon infusion on medium chain fatty acid into an isolated perfused rat heart, because -oxidation will feed electrons both via the NAD þ pool and ETF.…”
Section: Fluorescent Flavin Becomes a Compartment-speci¯c Mitochondrimentioning
confidence: 99%
See 1 more Smart Citation
“…40g molVI indicated iron or sulphate limitation with loss of ATP synthesis coupled to the NADH-ubiquinone oxidoreductase segment of the respiratory chain (Clegg & Light, 1971). Further confirmation of iron limitation was obtained by measuring the sensitivity of the NADH oxidase activity of submitochondrial particles to the respiratory inhibitor piericidin A; glycerol-limited cells yield submitochondrial particles that were sensitive to piericidin A, whereas those from iron-or sulphate-limited cells were insensitive (Ragan & Garland, 1971 These were made with a Varian E9 spectrometer operating at 9GHz (Varian Associates Ltd., Walton-on-Thames, Surrey, U.K.), with temperature control and measurement as described by Lowe et al (1972). Spectra were generally measured at a sample temperature of 12 ± 0.2°K and at 20 mW microwave power.…”
Section: Methodsmentioning
confidence: 96%